Analysis of permeability evolution law of gas-bearing coal under cyclic loading condition - Dengke WANG; Haohang FENG; Jianping WEI; Xu CHEN; Zhigang JIANG; Xiuzhu YUAN; Yun BAI; Tanggen CAO; Wenchao XIONG (Meitan kexue jishu)
In order to explore the permeability evolution law of gas-bearing coal under different cyclic loading and unloading conditions, raw coal samples were taken as the research object, and cyclic loading-unloading experiments of gas-bearing coal were designed and conducted using a triaxial creep-seepage experimental system under varying confining pressures and cyclic load upper limits. The permeability characteristics of gas-bearing coal under elastic cyclic loading and unloading and elastoplastic cyclic loading and unloading conditions were studied. The results show that for gas-bearing coal under different upper limits of cyclic loading, under the condition of elastic cyclic loading and unloading, the permeability decreases gradually with the increase of cycle times, the absolute permeability damage rate increases gradually, and the relative permeability damage rate decreases gradually；Under the condition of elastic-plastic cyclic loading and unloading, the permeability characteristics are different under different confining pressures with the increase of the number of cycles. Under high confining pressure, the permeability of gas-bearing coal still decreases gradually with the cycle, and under low confining pressure, the permeability of gas-bearing coal decreases with the cycle. The permeability damage rate of gas-bearing coal under high confining pressure is similar to that under elastic cyclic loading and unloading conditions. Under low confining pressure, the absolute permeability damage of gas-bearing coal first increases rapidly and then tends to be stable, and the relative permeability damage first decreases rapidly and then tends to be stable. Under the condition of elastic cyclic loading, the permeability stress sensitivity coefficient of gas-bearing coal in the loading stage and unloading stage decreases monotonously with the increase of the number of cycles. Under the condition of elastic-plastic loading, the permeability stress sensitivity coefficient of gas-bearing coal still shows a decreasing trend within a certain number of cycles, and then fluctuates and increases with the increase of cycles. In the loading stage, the permeability stress sensitivity coefficient decreases gradually with the cycle, and the permeability stress sensitivity coefficient increases gradually in the unloading stage. However, for the elastic-plastic cyclic loading and unloading conditions, the permeability stress sensitivity coefficient of gas-bearing coal decreases with the increase of confining pressure.